Bovine leukemia virus encoded blv-miR-b4-3p microRNA is associated with reduced expression of anti-oncogenic gene in vivo - Petersen, Marcos Iván (2023)
Bovine leukemia virus (BLV) is a retrovirus that causes malignant B-cell lymphoma in up to ten-percent of infected cattle. To date, the mechanisms of BLV linked to malignant transformation remain elusive. Although BLV-encoded miRNAs have been associated with the regulation of different genes involved in oncogenic pathways, this association has not been evaluated in cattle naturally infected with BLV. The objective of this study was to determine the relative expression of BLV-encoded miRNA blv-miR-b4-3p, the host analogous miRNA bo-miR-29a and a couple of potential target mRNAs (HBP-1 and PXDN, with anti-tumorigenic function in B-cells), in cattle naturally infected with BLV compared to uninfected animals (control group). We observed that PXDN was significantly downregulated in BLV-infected cattle (P = 0.03). Considering the similar expression of endogenous bo-miR-29a in both animal groups, the downregulation of PXDN in BLV-naturally infected cattle could be linked to blv-miR-b4-3p expression in these animals. Knowing that PXDN is involved in anti-tumoral pathways in B-cells, the results presented here suggest that blv-miR-b4-3p might be involved in BLV tumorigenesis during natural infection with BLV in cattle.